Describing Function Analysis of Systems with Impacts and Backlash - Barbosa, Ramiro (2002)
This paper analyzes the dynamical properties of systems with backlashand impact phenomena based on the describing function method. It isshown that this type of nonlinearity can be analyzed in the perspectiveof the fractional calculus theory. The fractional-order dynamics isillustrated using the Nyquist plot and the results are compared withthose of standard models.